UPAYA MENINGKATKAN KUALITAS MEMBACA AL-QURAN SANTRI MADRASAH - Nur Hasyikin; Ida Laila; Eko Nursalim (JOEL: Journal of Educational and Language Research, 2023)
This research is focused on enhancing the proficiency of students in Quranic reading. The methodology employed is Classroom Action Research, involving planning, implementation, observation, and reflection stages. Data collection encompasses interviews, observations, and testing. The study involved 16 third-grade students at School X. The findings suggest that the Quranic reading habituation method was effective, as each cycle showed an improvement in the percentage of results.